Hubungan Hasil Pemeriksaan Urinalisis dengan Kultur Urin untuk Deteksi Infeksi Saluran Kemih pada Ibu Hamil - Meta Safitri; Yustiana Arie Suwanto; Annisa Saffana Azmi Suryani; Arizkia Isnaeni Nurfadhillah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to determine the number of pregnant women at risk of urinary tract infection (UTI) based on urinalysis and urine culture examinations, as well as to identify risk factors associated with UTI. The research method used was an observational experimental study with urine culture and Dipstick test examinations. Urine culture was used as the gold standard with a bacterial count parameter of more than 105 CFU/ml, along with leukocyturia and nitrite detection in urine. The results showed a significant relationship between bacterial count and leukocyturia (p=0.001), but no significant association with the presence of nitrites in urine. Risk factors significantly associated with UTI included education level (p=0.037), frequency of holding urination (p=0.019), water intake (p=0.004), genital hygiene practices (p=0.003), water source (p=0.009), and leukocyte levels (p=0.001). Meanwhile, age, occupation, gestational age, and sexual activity did not show a significant relationship with UTI occurrence. In conclusion, pregnant women need to increase awareness of UTI risks and avoid factors that may contribute to infection to prevent pregnancy complications. Keywords: Urine Culture, Leukocyturia, Nitrite